Relationship between fertilization rate and early apoptosis in sperm population of infertile individuals. (7th November 2012) - Tavalaee, M.; Deemeh, M. R.; Arbabian, M.; Kiyani, A.; Nasr‐Esfahani, M. H.
Summary Integrity of the sperm membrane, of which phosphatidyl serine (PS) plays a central role, is essential for fertilization. The externalisation of PS (EPS) occurs during capacitation and the acrosome reaction. EPS, from the inner to the outer membrane, is considered as a sign of early apoptosis. Therefore, EPS may have a dual function in sperm. This study has evaluated the relationship between EPS and fertilization, embryo quality and pregnancy outcomes in couples who were candidates for ICSI. Semen samples were collected from 43 ICSI candidates and assessed according to World Health Organization guidelines for semen parameters. EPS was assessed by Annexin V and propidium iodide (PI) staining. Protamine deficiency was assessed by chromomycin A3 (CMA3) staining. A significant positive correlation was observed between the percentages of fertilization and annexin‐positive PI‐negative (An+PI−) sperm. There was a significant negative correlation between the percentages of protamine‐deficient sperm with the percentage of fertilization. In addition, the percentage of An+PI− sperm in individuals with fertilization rates higher and lower than 50% significantly differed. The percentage of annexin‐positive PI‐positive (An+PI+) sperm in semen of the partners of pregnant women significantly differed from the partners of nonpregnant women. In conclusion, if An+PI− is a sign of capacitation and An+PI+ is a sign of apoptosis, the results suggest that semen samples with a higher ability to undergo capacitation have a higher chance to result in successful fertilization post‐ICSI. The presence of a high percentage of apoptotic sperm in the insemination sample before capacitation may reduce the chances of pregnancy.